Pulmonary artery stent for bronchial adenoid cystic carcinoma causing pulmonary artery stenosis. Issue 1 (21st January 2014) - Smith, Corey Allister; Kotlyar, Eugene; Mellemkjaer, Soren; Muller, David; Stone, Emily
Abstract A 46‐year‐old woman presented with a 6‐month history of dyspnea and weight loss on a background of previous pneumonectomy for bronchial adenoid cystic carcinoma 14 years beforehand. Several years prior to this presentation, she had developed left vocal cord palsy and a metastatic lesion to the right buttock confirmed at resection. Investigations included CT pulmonary angiography and right heart catheterisation and demonstrated pulmonary artery stenosis suggestive of vascular encasement, severe pulmonary arterial hypertension and pulmonary nodules. Subsequent pulmonary artery stenting markedly improved both pulmonary artery pressures and the patient's symptoms. The diagnosis of pulmonary artery stenosis due to mediastinal infiltration by metastatic bronchial adenoid cystic carcinoma was based on these findings as well as the presence of the pulmonary nodules and the previous mediastinal (recurrent laryngeal nerve) and metastatic complications. This case is the first report of successful pulmonary artery stenting for this rare complication.